Strong Karleman averages of multiple trigonometric Furier series - Kuznetsova , О. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We prove the strong Carleman summability of the Fourier series of continuous functions on the m-dimensional torus, with partial sums constructed over polyhedra of a certain class.